What nutrition advice is freely available for gymnasts, coaches and parents on their member National Governing Body webpages? - Jessica Riman; Karen M Keane
The purpose of this content analysis was to ascertain what nutrition advice or information is freely available on a global scale through each National Governing Body (NGB) webpage. In total, 52 NGBs and the International Federation of Gymnastics (FIG) were identified based on the FIG November 2022 world rankings for both male and female athletes in all disciplines. Concluding observations were that publicly available nutrition advice is limited across the global gymnastics platforms. Conflicting advice was also identified within some organisations surrounding the weighing of gymnasts for hydration purposes and some macronutrient discrepancies thus, potentially impacting the clarity of the message for the reader. Based on this content analysis recommendations for future practice include providing clarity and provision of tools to measure hydration, dietary recommendations should be clear and specific, and a more centralised approach to standardise advice and publicly available information.